2000
DOI: 10.1073/pnas.050417697
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of immune responses to HIV-1 and simian immunodeficiency virus DNA vaccines by IL-2/Ig plasmid administration in rhesus monkeys

Abstract: The potential utility of plasmid DNA as an HIV-1 vaccination modality currently is an area of active investigation. However, recent studies have raised doubts as to whether plasmid DNA alone will elicit immune responses of sufficient magnitude to protect against pathogenic AIDS virus challenges. We therefore investigated whether DNA vaccine-elicited immune responses in rhesus monkeys could be augmented by using either an IL-2͞Ig fusion protein or a plasmid expressing IL-2͞Ig. Sixteen monkeys, divided into four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(113 citation statements)
references
References 39 publications
3
109
0
1
Order By: Relevance
“…A study conducted in nonhuman primates immunized i.m. demonstrates that the administration of a plasmid expressing human IL-2/Ig can substantially augment vaccine-elicited humoral and cellular immune responses (37). A similar study showed that IL-2 or IL-4 could increase the humoral responses to HIV Ags upon i.m.…”
Section: S Tudies Of Virus-specific Immune Responses In Hiv-exposedmentioning
confidence: 55%
“…A study conducted in nonhuman primates immunized i.m. demonstrates that the administration of a plasmid expressing human IL-2/Ig can substantially augment vaccine-elicited humoral and cellular immune responses (37). A similar study showed that IL-2 or IL-4 could increase the humoral responses to HIV Ags upon i.m.…”
Section: S Tudies Of Virus-specific Immune Responses In Hiv-exposedmentioning
confidence: 55%
“…Such approaches would have to minimize potential integration problems inherent in DNA vaccines that express cellular proteins as part of vaccine adjuvants. It is interesting to note that DNA vaccines delivered with IL-2 Ig (a cellular cytokine protein) DNA achieved great potency in eliciting HIV-specific CD8 ϩ T cell responses in rhesus macaques (70).…”
Section: Discussionmentioning
confidence: 99%
“…Letvin and colleagues showed that monkeys immunized with DNA encoding both the HIV Ags and a form of IL-2 increased cellular immune responses and resistance to disease following challenge with a pathogenic simian-human immunodeficiency virus. Administration of recombinant exogenous IL-2 has given more mixed results (21)(22)(23). Because detailed studies of pharmacokinetics and biodistribution of the recombinant cytokines and cytokine gene products have not usually been done in concert with the studies of immune responses, it has proven difficult to translate these results across species and into different experimental models.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%